1998
DOI: 10.1093/jnci/90.14.1087
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Inhibition of Renal Cancer Growth by Anti-Epidermal Growth Factor Receptor Antibody and Protein Kinase A Antisense Oligonucleotide

Abstract: The combination of anti-EGFR MAb C225 and ited cooperative antiproliferative effects and cooperative antitumor effects on EGFR and PKAI-expressing human renal cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 32 publications
2
24
0
1
Order By: Relevance
“…Consistent with this model is the observation that interfering with the TGF-␣͞EGFR circuit significantly reduced the ability of VHL Ϫ/Ϫ RCC cells to grow in low serum without correcting other cellular defects associated with the loss of VHL function, such as HIF␣ overexpression and failure to assemble an extracellular fibronectin matrix. Inhibition of the EGFR receptor also prevents RCC tumor formation in nude mice, in agreement with our data (34,35). However, it remains to be shown whether the unregulated growth of VHL Ϫ/Ϫ RCC cells is solely the consequence of the establishment of a TGF-␣͞EGFR growthstimulatory circuit or whether other defects are involved in this process.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this model is the observation that interfering with the TGF-␣͞EGFR circuit significantly reduced the ability of VHL Ϫ/Ϫ RCC cells to grow in low serum without correcting other cellular defects associated with the loss of VHL function, such as HIF␣ overexpression and failure to assemble an extracellular fibronectin matrix. Inhibition of the EGFR receptor also prevents RCC tumor formation in nude mice, in agreement with our data (34,35). However, it remains to be shown whether the unregulated growth of VHL Ϫ/Ϫ RCC cells is solely the consequence of the establishment of a TGF-␣͞EGFR growthstimulatory circuit or whether other defects are involved in this process.…”
Section: Discussionsupporting
confidence: 92%
“…Anti-EGFR antibodies have been shown to inhibit growth of EGFR-overexpressing tumor cells (15). Mab C225, an anti-EGFR humanized chimeric monoclonal antibody, can delay tumor growth in ACHN human renal cancer cell tumor xenografts (16). Activation of EGFR-TK causes downstream cellular substrates to become phosphorylated on tyrosine, and these are implicated in cancer cell proliferation and survival (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…34,56 Previous reports combining TGF-␣ antisense oligonucleotides with an EGFR-specific tyrosine kinase inhibitor or a protein kinase A inhibitor in vitro, suggested that increased growth inhibition could be achieved by targeting the ligand simultaneously with a downstream signaling peptide. 41,57 TGF-␣ antisense oligonucleotides have also been used in conjunction with one of several chemotherapy agents where combined treatment demonstrated increased growth inhibition of colon cancer cells compared with TGF-␣ antisense oligonucleotide alone. 58 Treatments designed to abrogate TGF-␣ production represent a potential means of inhibiting tumor growth in cancers which overexpress this growth factor.…”
Section: Discussionmentioning
confidence: 99%